Metallothionein gene polymorphism associated with Cd and Hg levels in non-obstructive azoospermia patients: a hospital-based observational study - Sharma, Nisha; Halder, Ashutosh; Kaushal, Seema; Kumar, Manoj; Jain, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Heavy metals, such as Cadmium (Cd), Arsenic (As), Mercury (Hg) and Lead (Pb) might potentially induce reproductive toxicity in male infertility patients, regardless of the varying concentrations of these heavy metals in the blood. Genetic polymorphism is one of the least studied internal contributing factors in male infertility cases associated with high level of heavy metal in blood. Therefore, this study aims at identifying the difference in the serum levels of heavy metals in non-obstructive azoospermia (NOA) patients associated with genetic variants. Methods: It’s a hospital based observational study where patients reporting with azoospermia due to hypospermatogenesis (HS) were recruited prospectively. Comprehensive clinical history, and blood samples were collected. Whole exome sequencing (WES) and was performed for 50 HS patients to identify variants. Inductively coupled plasma mass spectrometry (ICP-MS) was performed to assess levels of Cd, As, Hg and Pb levels in serum samples of 50 HS patients. Statistical analysis was performed to determine difference in heavy metal concentration of HS patients with and without the presence of metallothionein gene associated single nucleotide polymorphism (SNP). Results: Genomic analysis for SNPs identified deleterious candidate variants in MT1A (rs11640851 and rs8052394) associated with 18/50, MT1E (rs138690474) associated with 4/50 and MT4 (rs11643815) associated with 5/50 HS patients. A statistically significant difference in the blood concentration of Cd and Hg was observed in HS patients associated with metallothionein gene SNPs. Conclusions: This exploratory genomic analysis conducted on HS patients shows prevalence of deleterious candidate SNPs in metallothionein gene. The HS patients with candidate SNPs showed higher levels of Cd and Hg which indicate the genomic susceptibly towards heavy metal-induced reproductive toxicity.